The Case of Paedophiles in Indonesia: An Affective Study Towards Education Policy - Harianto Harianto (Madrosatuna: Journal of Islamic Elementary School, 2017)
Phenomenon in the year 2016 recorded cases of "pedophile" in Indonesia such as: Sarno (46) in Duren Sawit Jakarta, Andri Sobari alias Emon (Sukabumi) conduct pedophile about 114 children, at Jakarta International School, Samai and Sodikin (Tegal), Bali And Batam. The problem is how the affective study of the case of Paedofil in Indonesia towards the Education Policy? The purpose of this paper answers the following questions: Can a pedophile case affect the moral destruction of a nation? Does the pedophile case affect the deterioration of the nation's achievement? What is the moral evaluation of pedophilia? How does an exemplary figure's education answer the issue of a pedophile case ?. First, the case of pedophile greatly affect the impact of destroying the nation's morale and destroy the achievements of the nation's children in education. Secondly, the teacher should not have an abnormal life (being a pedophile). He is a picture of tekadan for his students. Thus the failure of teaching and learning process will occur when teacher teachers become "scourge" which is frightening for their students. Third, teachers become role models for their students. Master is a portrait of the future picture of the nation.